Analysis of ECJ case law on discriminatory treatment of cross-border inheritance tax - Gracia Luchena (Bratislava Law Review, 2017)
Recently, the European Commission has launched a package which deals with issues of double taxation and discriminatory tax treatment in the area of inheritance and estate tax. In the paper the Commission discusses ten cases in which the European Court of Justice examined the inheritance tax rules of Member States. In eight out of the ten cases it concluded that the Member States in question breached EU rules on the free movement of capital and/or freedom of establishment. For example, on the 3rd of September 2014, the ECJ entered/made a judgment resolving that the Spanish Inheritance Tax should impose restrictions on the free movement of capital, one of the fundamental principles of the EU’s Single Market. Taking into consideration the merits of the case the Court of Justice finally concluded that the situations between resident and non-resident taxpayers or between goods located in Spain or abroad are comparable and that therefore the applicable tax treatment should be the same.